2015
DOI: 10.17341/gummfd.92619
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Cu İki̇li̇ Alaşimlarinin Kutu Borlama Davranişina Bakir Mi̇ktarinin Etki̇si̇

Abstract: ÖZETİçerisine atomik olarak % 1, 2, 4, 8 ve 16 bakır katkılandırılarak hazırlanan Fe-Cu ikili alaşımları ve saf demir 1000°C' de 3 saat süre ile kutu borlama işlemine tabi tutulmuştur. Elde edilen borür tabakanın faz içeriği, mikroyapısı, kimyasal kompozisyonu ve mikrosertliği, X-ışınları kırınımı, Yüzey Taramalı Elektron Mikroskobunda Enerji Dağılımlı X-ışınları Spektroskopisi (SEM-EDS) ve Vickers Mikrosertlik ölçümü ile karakterize edilmiştir. Altlıktaki Cu miktarının artmasıyla borür tabakasının morfolojisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…2). The same precipitates have been also obtained on borided Fe8Cu alloys [31], where it was shown that light gray region, has high amounts of Cu and relatively less amounts of Fe. In this figure, it is possible to observe how the hardness of borided samples changes from the boride layer to matrix.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…2). The same precipitates have been also obtained on borided Fe8Cu alloys [31], where it was shown that light gray region, has high amounts of Cu and relatively less amounts of Fe. In this figure, it is possible to observe how the hardness of borided samples changes from the boride layer to matrix.…”
Section: Resultssupporting
confidence: 60%
“…The obtained thickness values were 138, 90, and 36 µm for A, B, and C shape memory alloys, respectively (Table II). Conversely, it has been shown that the Cu does not significantly affect the boride layer thickness while Si as an alloying element in the substrate considerably decreases boride layer thickness in borided Fe-8Si [30] and Fe-8Cu [31] binary alloys. On the other hand, the porosity was seen in the boride layer of the samples.…”
Section: Resultsmentioning
confidence: 99%